The evaluation of different types fecal bacteria products for the treatment of recurrent Clostridium difficile associated diarrhea: A systematic review and network meta-analysis - Yang, Liping; Li, Wenrui; Zhang, Xianzhuo; Tian, Jinhui; Ma, Xiaojia; Han, Lulu; Wei, Huaping; Meng, Wenbo (Frontiers in Surgery, 2022)
Abstract Purpose: To determine the efficacy of different types of fecal microbiota transplantation for the treatment of diarrhea associated with rCDI. Methods: We searched PubMed, Embase, The Cochrane Library, Web of Science, CBM (China Biomedical Medicine), China National Knowledge Infrastructure (CNKI) and WanFang database. We also tracked the references found in systematic reviews of CDI-associated diarrhea treated with fecal microbiota transplantation. We included randomized controlled trials (RCTs) comparing different types of fecal microbiota transplantation with other methods for the treatment of rCDI-related diarrhea. The search period was from the date of inception of this treatment method to January 16, 2022. Two reviewers independently screened the published literature, extracted the data and assessed the risk of bias. Systematic review and network meta-analysis were conducted using RevMan 5.4, R4.1.2 and Stata 16.0 software. Results: Ten RCTs involving 765 patients were included in this network meta-analysis. The results showed that treatment with fresh fecal bacteria was better than vancomycin [odds ratio, (OR)=13.66, 95% confidence interval (95% CI) (1.51, 167.61)]. However, there were no statistically significant differences in recovery rate [fresh vs frozen: OR=1.91, 95% CI (0.18, 35.78); fresh vs lyophilized, OR=3.78, 95% CI (0.18, 166.88); frozen vs lyophilized, OR=2, 95% CI (0.16, 28.2)]. The SUCRA indicated that fresh fecal bacteria were the best treatment for rCDI-related diarrhea. Conclusions: Fresh fecal bacteria was the best treatment of diarrhea associated with rCDI, but frozen fecal bacteria and lyophilized fecal bacteria can achieve the same effect, which was worthy of clinical and commercial application.